Paciente de sexo femenino de 53 años de edad con gastritis aguda e hiperlipidemia mixta. - Del Rosario Torres, Génesis Valeria (2021)
The present clinical case deals with a 53-year-old female patient with a diagnosis of acute gastritis and mixed hyperlipidemia who comes to the consultation due to pain in the upper abdomen, decreased appetite, general malaise, paleness, and fatigue. who has a personal history of epigastric pain, does not drink alcohol, and is not allergic to any medications. A nutritional intervention is carried out to prevent the progression of the disease and future complications with the aim of improving the quality of life of the patient with gastritis and mixed hyperlipidemia through a nutritional process according to the progress of the present pathologies. In the anthropometric evaluation we have a weight of 56 kg and a height of 155 cm, abdominal circumference of 77 cm which reflects a normal nutritional status according to the WHO with a BMI of 23.3 kg / m2. Regarding the biochemical evaluation, there is evidence of an alteration in the lipid profile with high levels of cholesterol and triglycerides that indicates hypercholesterolemia and hypertriglyceridemia. A 1200 kcal hypo-fat diet is prescribed, divided into 5 meal times, warm temperature, and moderate volume. The progression of complications was stopped by the nutritional care process. A control of the therapeutic diet plan is maintained. According to the follow-up, it was observed that, through the assessment, diagnosis and nutritional intervention, the patient presents favorable changes in terms of her condition and nutritional status.